A typical anterior retinoblastoma: diagnosis by aqueous humor cell-free DNA analysis. (2nd November 2022) - Kletke, Stephanie N.; Soliman, Sameh; Racher, Hilary; Mallipatna, Ashwin; Shaikh, Furqan; Mireskandari, Kamiar; Gallie, Brenda L.
ABSTRACT: Background: Aqueous humor from eyes with active retinoblastoma contains tumor-derived cell-free DNA. Materials and Methods: Single retrospective case report. Results: A 13-year-old girl with acute right eye pain and redness was diagnosed with hypertensive anterior uveitis. Following initial management, she was referred to ocular oncology for an atypical clinical picture. Multiple seeds were noted 360 degrees in the anterior chamber, at the equator of the lens and canal of Petit, and ultrasound biomicroscopy identified a temporal pars plana lesion. While aqueous humor cytology was inconclusive for malignancy, targeted next-generation sequencing of aqueous cell-free DNA identified biallelic RB1 full gene deletion, confirming the diagnosis of retinoblastoma. Partial regression followed three cycles of systemic carboplatin, etoposide, and vincristine and three intracameral melphalan injections. Four months later, she had recurrence of the primary tumor and increase in seeding and received the investigational sustained release episcleral topotecan chemoplaque. Stable regression was achieved to 28-month follow-up, with no detectable aqueous cell-free DNA. Conclusions: RB1 sequencing analysis of tumor-derived cell-free DNA from aqueous humor can confirm the diagnosis of retinoblastoma in cases of diagnostic uncertainty.